Dolokumma in the Kirat Rai Philosophy: Ritual Continuity or Cosmic Creation - Rai, Shanti Devi; Rai, Purna Bahadur Jeeten (Kirat Pragya किरात प्रज्ञा, 2026)
This paper discovers the position of Dolokumma as the ancient creator and cosmic custodian in Mundum philosophy, central to Kirat Rai identity and ritual continuity. Through the Mundumic Risiya (mantra), Mundumic story, sacred dance, sacred song, genealogies and ritual performance Dolokumma accumulate human origin and nature nurturing wisdom. Existence of Ribhyama, Naima, Sumnima represents continuity of generation to generation. In Mundum philosophy, Suptulung shrine assist as a sacred place for communication between visible and invisible soul. This holy place is their educational agency. Nonetheless, colonial practice disrupted intergenerational learning, risk native land, ritual, identity, language, and legacy. This study argues that, urgently need to document aural Mundumic knowledge, and traditional practices. The Risiya of Dolokumma, emphases to sustaining harmony earth and sky. From primeval period affirms women’s central act in ritual continuity and cosmic creation.